2009
DOI: 10.1017/s0266467408005695
|View full text |Cite
|
Sign up to set email alerts
|

Does desiccation risk drive the distribution of juvenile cane toads (Bufo marinus) in tropical Australia?

Abstract: Abstract:Immediately after their transition from aquatic to terrestrial life, juveniles of many anuran species are restricted to the margins of natal ponds. Understanding the factors determining the duration of that pondside aggregation has direct management ramifications in the case of the invasive cane toad (Bufo marinus) in tropical Australia. Previous work suggests that dispersal confers biotic advantages (reduced risk of cannibalism, enhanced feeding opportunities) to juvenile toads, but desiccation risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Cane toads breed in temporary and permanent ponds across this area, spawning most frequently at the end of the wet-season, as pond levels begin to fall; but they also can breed during the dry season [42], (M. R. Crossland and E. Cabrera-Guzmán unpublished data). Toad metamorphs (the first terrestrial phase, immediately after transformation from the tadpole) are mainly diurnal [62] and remain near the edge of natal ponds during the dry season [63]. They disperse through the wider landscape during the wet season [51], [63], [64] but often remain close to the pond from which they emerged [52].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cane toads breed in temporary and permanent ponds across this area, spawning most frequently at the end of the wet-season, as pond levels begin to fall; but they also can breed during the dry season [42], (M. R. Crossland and E. Cabrera-Guzmán unpublished data). Toad metamorphs (the first terrestrial phase, immediately after transformation from the tadpole) are mainly diurnal [62] and remain near the edge of natal ponds during the dry season [63]. They disperse through the wider landscape during the wet season [51], [63], [64] but often remain close to the pond from which they emerged [52].…”
Section: Methodsmentioning
confidence: 99%
“…Toad metamorphs (the first terrestrial phase, immediately after transformation from the tadpole) are mainly diurnal [62] and remain near the edge of natal ponds during the dry season [63]. They disperse through the wider landscape during the wet season [51], [63], [64] but often remain close to the pond from which they emerged [52]. Juvenile toads become increasingly nocturnal.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that agar models provide robust estimates of water exchange rates in free-living cane toads in our study areas [27], [35], [36]. Our enclosures were situated within an area containing abundant free-living toads (and farms, and thus manure), and it is difficult to see why the facilitation of food supply offered by our artificial cowpats would not occur in nature also.…”
Section: Discussionmentioning
confidence: 98%
“…In our lab trials we deliberately chose small toads to minimize mortality in the snakes, but no such mechanism operated in the field. Additionally, small toads are concentrated around waterbody fringes, especially during the dry season (Child et al, 2008;Child, Phillips & Shine, 2009), and thus may not be encountered by death adders in other habitat types. In contrast, large toads are widely distributed.…”
Section: Discussionmentioning
confidence: 99%